Marketing Strategies of Fashion Brands in the New Media Era - Zhong, Wanyi (Transactions on Economics, Business and Management Research, 2024)
In today’s development context, the issues that arise in the process of corporate brand marketing are no longer limited to product problems but have expanded to communication problems. With the advent of the new media era, the way people obtain information has changed significantly, accelerating the innovation of Chinese enterprises in brand marketing. The widespread use of the internet and the increasing number of internet users have accelerated the rapid development of new media, while also posing significant challenges to traditional media. Therefore, in the context of the internet, due to changes in the channels and methods of information dissemination, the information market has gradually exhibited personalized demand characteristics. The development of new media presents both opportunities and challenges for enterprises, especially for some fashion brands. The emergence of new media directly affects their future development direction and brings considerable competitive pressure. Based on this, this paper provides a detailed analysis of the marketing strategies of fashion brands in the new media era, hoping to be of help to relevant personnel.